Identifikasi miskonsepsi siswa dalam menyelesaikan masalah program linier berdasarkan metode Newman ditinjau dari Gender - Tyaningsih, Ratna Yulis; Novitasari, Dwi; Salsabila, Nilza Humaira (Pendidikan Matematika FKIP Universitas Mataram, 2025)
Misconceptions in solving linear programming problems remain a challenge in mathematics education. Conceptual errors made by students can lead to misunderstandings and suboptimal learning outcomes. This study aims to identify students' misconceptions in solving linear programming problems based on the Newman method and analyze them from a gender perspective. The research method used is qualitative descriptive, with research subjects consisting of high school students who have studied linear programming. Data were collected through a diagnostic test based on the Newman method and in-depth interviews. The Newman method was used to analyze students' errors in five stages: reading, comprehension, transformation, process skills, and writing the final answer. The results showed that misconceptions most frequently occurred in the transformation and process skills stages. Male students tended to make errors in process skills, while female students made more mistakes in the comprehension and transformation stages. The conclusion of this study indicates that gender influences students' misconception patterns in solving linear programming problems. These findings are expected to serve as a reference for educators in designing more effective teaching strategies to reduce misconceptions and improve students' understanding of linear programming.